The global minotaur : America, Europe and the future of the global economy - Varoufakis, Yanis (London Zed Books, 2015)
The author explodes the myth that financialization, ineffectual regulation of banks, greed and globalization were the root causes of the global economic crisis. Rather, they are symptoms of a much deeper malaise which can be traced all the way back to the Great Crash of 1929, then on through to the 1970s: the time when a 'Global Minotaur' was born. Just as the Athenians maintained a steady flow of tributes to the Cretan beast, so the 'rest of the world' began sending incredible amounts of capital to America and Wall Street. Thus, the Global Minotaur became the 'engine' that pulled the world economy from the early 1980s to 2008. Today's crisis in Europe, the heated debates about austerity versus further fiscal stimuli in the US, the clash between China's authorities and the Obama administration on exchange rates are the inevitable symptoms of the weakening Minotaur; of a global 'system' which is now as unsustainable as it is imbalanced. Going beyond this, the author lays out the options available to us for reintroducing a modicum of reason into a highly irrational global economic order.
Includes bibliographical references (pages 257-271) and index.
Keywords: International finance--History--20th century